Canadian Observatory on the Justice System's Response to Intimate Partner Violence - Gill, Carmen (Atlantis, 2006)
This article discusses a national partnership of Canadian Research Centres on Violence ("the Alliance") and its approach, as the group moves toward developing a Canadian observatory, its goals and research priorities.